2021
DOI: 10.1039/d1ra01353j
|View full text |Cite
|
Sign up to set email alerts
|

Novel procedure of CO2 capture of the CaO sorbent activator on the reaction of one-part alkali-activated slag

Abstract: The proposed strategy builds a bridge between the alkali-activated cement and CaO-based CO2 sorbents, and this study provides a facile and cost-effective method for controlling the reaction rate of alkali-activated slag.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…All curves indicated that decomposition mainly occurred in the second stage and was complete at about 800 °C. The weight loss found from the TGA measurements agreed fairly well with that expected for the decomposition of hydroxy carbonates (M2CO3(OH)2) to different oxides of Ca and Ce [39,40]. TGA analysis was used to investigate the thermal stability of the CaO, CeO 2 , and xCaO@CeO 2 catalysts, showing a gradual and complex degradation process (Figure 5).…”
Section: Catalysts Characterizationsupporting
confidence: 72%
“…All curves indicated that decomposition mainly occurred in the second stage and was complete at about 800 °C. The weight loss found from the TGA measurements agreed fairly well with that expected for the decomposition of hydroxy carbonates (M2CO3(OH)2) to different oxides of Ca and Ce [39,40]. TGA analysis was used to investigate the thermal stability of the CaO, CeO 2 , and xCaO@CeO 2 catalysts, showing a gradual and complex degradation process (Figure 5).…”
Section: Catalysts Characterizationsupporting
confidence: 72%
“…Future studies can find ways to clean up the production of synthetic solid activators. For instance, a recent study on GGBS-based one-part mixes activated using CaO used solid activators for carbon capture with promising results [208]. Alternatively, solid activators from waste products can be used.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…As the amount of filler increased, so did the conductivity. Wood ashes, as other studies [ 36 ] and XRF analysis confirmed, are rich in CaO that in an aqueous solution can convert into Ca(OH) 2 and dissociate in Ca 2+ and 2OH − [ 37 ]. The former contributes to increasing the conductivity, and the latter increases the pH values.…”
Section: Resultsmentioning
confidence: 99%